Does monsoon gyre always favour tropical cyclone rapid intensification?. (19th July 2019) - Yan, Ziyu; Ge, Xuyang; Peng, Melinda; Li, Tim
Abstract: In this study, potential impacts of monsoon gyres (MG) on the development of a tropical cyclone (TC) are investigated using idealized numerical simulations. When a TC is embedded in an MG, our results show that its development is slower, and its intensity is weaker compared with that evolved with no background flow. We identified three MG dynamic mechanisms that can affect TC development. First, the superposition of TC and MG circulations produce a larger outer size for the TC. A TC with a larger size develops slowly and has a reduced capacity to organize convection through vorticity segregation process. Deep convection is located mainly outside the radius of maximum wind, resulting in slower intensification rates. Secondly, when the TC is embedded on the eastern flank of the MG, its outer profile becomes barotropically unstable. The asymmetric perturbations exhibit an up‐shear tilting, which extracts kinetic energy from the primary vortex and thus hinders TC intensification. In the third mechanism, the vertical baroclinic nature of the MG imposes an ambient vertical wind shear on the TC, leading to a vertical tilting and increased asymmetric perturbation that hinders TC intensification. The MG relative humidity also impacts TC intensification, with negative impacts greater in drier environments. Abstract :